2020
DOI: 10.1037/stl0000167
|View full text |Cite
|
Sign up to set email alerts
|

Assessing student learning and knowledge transfer using principles of team-based learning and bridge assignments in large introductory statistics classes.

Abstract: Undergraduate psychology students enrolled in an introductory statistics course often experience difficulty due to math anxiety, insufficient preparation, and large impersonal classes, all of which threaten their ability to pass the course and acquire the knowledge and skills they need to be successful in the subsequent research methods class. This research compared the performance of 296 students taking an introductory statistics course that incorporated team-based learning (TBL) and other evidence-based inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Both students and instructors have revealed high levels of satisfaction using TBL for statistical literacy (St. Clair & Chihara, 2012). In addition, students have experienced improved performance and reported that TBL had a positive impact on their learning of statistics (Campbell & Taylor, 2020).…”
Section: Adapting Tbl To Undergraduate Online Mathematics and Statisticsmentioning
confidence: 99%
“…Both students and instructors have revealed high levels of satisfaction using TBL for statistical literacy (St. Clair & Chihara, 2012). In addition, students have experienced improved performance and reported that TBL had a positive impact on their learning of statistics (Campbell & Taylor, 2020).…”
Section: Adapting Tbl To Undergraduate Online Mathematics and Statisticsmentioning
confidence: 99%
“…Some of these programmes are not only qualitative in nature but are also quantitative or mathematically inclined. According to Campbell and Taylor [10], mathematics related courses are noted to cause stirs in the minds of students. It often leads to significant concerns for students and affects students learning capabilities and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Students are especially anxious about research methods and statistics courses and this anxiety can lead to avoidance behaviors (Macher et al, 2013; Onwuegbuzie & Wilson, 2003). When coupled with low self-efficacy and maladaptive behaviors and attitudes towards math and statistics, such combinations threaten students’ academic progress often resulting in high DFW rates in the very classes that are gateways into social and behavioral professions (Campbell & Taylor, 2019). To buffer against such undesirable outcomes, UTAs are useful, albeit underutilized resources, especially given the range of duties they can perform: workshop implementation, tutoring, grading, facilitating in-class activities, and holding office hours (Filz & Gurung, 2013).…”
Section: Introductionmentioning
confidence: 99%